Endoscopic thyroidectomy via areola approach for stage T1 papillary thyroid carcinoma: feasibility, safety, and oncologic outcomes - Huo, Jinlong; Xu, Yaxuan; Yu, Jie; Guo, Youming; Hu, Xiaochi; Ou, Dong; Qu, Rui; Zhao, Lijin (Frontiers in Endocrinology, 2023)
Purpose To evaluate the feasibility, safety, and oncologic outcomes associated with endoscopic thyroidectomy via the areolar approach (ETAA), compared with conventional open thyroidectomy (COT) for the treatment of stage T1 papillary thyroid carcinoma (PTC). Methods Between January 2021 and June 2022, a total of 1204 patients diagnosed with PTC underwent screening, out of which 138 patients were selected for inclusion in the study population after propensity score matching (92 patients in the ETAA group and 46 patients in the COT group). The study included the collection and analysis of clinicopathologic characteristics, intraoperative outcomes, postoperative outcomes, complications, and follow-up data using R software. Results The operative time for the ETAA group was longer than that for the COT group (160.42 ± 32.21 min vs. 121.93 ± 29.78 min, p < 0.0001). However, there were no significant differences between the two groups in terms of intraoperative blood loss, the extent of surgical resection, the number of dissected lymph nodes, the number of metastatic lymph nodes, and the rate of parathyroid autotransplantation. Postoperative drainage and C-reactive protein levels were higher in the ETAA group than in the COT group, but there were no significant differences in 24-hour visual analogue scale scores, white blood cell counts, drainage duration, or postoperative hospital stay. Complication rates were similar between the two groups, and no permanent recurrent laryngeal nerve palsy or hypoparathyroidism was observed. Patients who underwent ETAA reported greater cosmetic satisfaction and quality of life than those who underwent COT. During the follow-up phase, only one patient in the COT group developed lateral cervical lymph node involvement requiring reoperation. Conclusion ETAA is a safe and feasible surgical method for patients with stage T1 PTC, providing results similar to COT in terms of oncologic completeness, while avoiding neck scars, with excellent cosmetic effects. Clinical trial registration Chinese Clinical Trial Registry center, identifier ChiCTR2300077109